Metabolizable energy values of soybean meals and soybean oil for broilers at different ages - Antônio Gilberto Bertechini (Acta Scientiarum. Animal Sciences, 2019)
One trial with six analyses of different diets at different ages was carried out to determine the values of apparent (AME), corrected (AMEn), true (TME) and true corrected (TMEn) metabolizable energy of SBM and SBO for broiler chickens from 1 to 42 days of age. Three Brazilian SBM samples and one SBO were evaluated by replacing part of the basal diet with the test ingredient (300 g kg-1 for SBM and 100 g kg-1 for SBO). A total of 1.368 one-day-old male Ross 308 birds were assigned into 36 metabolic cages according to weight in a completely randomized experimental design with six replicates for each test ingredient and basal diet. Six more replicates of fasted birds were used for the determination of metabolic energy and N losses at each age. Four days of adaptation followed by three days of excreta collection for energy measurement. The birds were reared until each age, in solid floor pens with a corn/soybean basal diet. The total excreta collection method was used. The AME, AMEn, TME and TMEn of SBM and SBO increased (p < 0.05) until 28 days and after this time no difference (p >0.05) was observed.